Pengaruh Strategi Pemasaran Terhadap Keputusan Masyarakat Pembelian Produk Usaha Mikro Kecil Dan Menengah Di Kabupaten Tapanuli Selatan - Mukti Simamora; Hazmanan Khair (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study was to examine and analyze the effect of product, price, place, promotion on purchasing decisions in South Tapanuli Regency partially or simultaneously. The approach used in this study is a quantitative approach. The population in this study is all people who buy the product. The sample in this study used quota sampling totaling 100 people who bought MSME products. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study is the classical assumption test, multiple linear regression Hypothesis Testing and the coefficient of determination. Data processing in this study using the SPSS software program. The results of this study prove that partially and simultaneously product, price, place and promotion have a significant effect on purchasing decisions